2018
DOI: 10.4236/jmmce.2018.63020
|View full text |Cite
|
Sign up to set email alerts
|

Hydrometallurgical Processing of a Nigerian Galena Ore in Nitric Acid: Characterization and Dissolution Kinetics

Abstract: The physico-chemical characterization and dissolution kinetics study of a Nigerian galena ore in nitric acid has been undertaken. The effects of acid concentration, temperature, particle size, stirring speed and solid/liquid ratio on the leaching of galena were investigated. The X-ray fluorescence data showed that the galena ore used in the study exists mainly as PbS. Lead (Pb) was detected as the major metal for galena with metals such as Na, Ca, Fe, Zn, Al and Mg occurring as minor elements. The XRD analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…Herein, all the peaks observed in the orange curve were attributed to the barite sample in agreement with previous reports. , Similarly, the results for celestite (shown in green) are supported by previous literature reports. , With regard to sulfide scales, XRD confirmed that the sample used herein is pure PbS. All the peaks, shown in purple at 2 theta of 26, 30, 43.5, 51, 63, 69, and 71° are for PbS. Pyrite sample results are given elsewhere, whereas the four peaks at 30, 34.5, 44, and 53.5° (in red color) are for pyrrhotite. Finally, carbonate scales are studied using the CaCO 3 sample with the XRD peaks illustrated in black and are in agreement with the published literature. , All samples were pure minerals as confirmed by the XRD results.…”
Section: Resultssupporting
confidence: 91%
“…Herein, all the peaks observed in the orange curve were attributed to the barite sample in agreement with previous reports. , Similarly, the results for celestite (shown in green) are supported by previous literature reports. , With regard to sulfide scales, XRD confirmed that the sample used herein is pure PbS. All the peaks, shown in purple at 2 theta of 26, 30, 43.5, 51, 63, 69, and 71° are for PbS. Pyrite sample results are given elsewhere, whereas the four peaks at 30, 34.5, 44, and 53.5° (in red color) are for pyrrhotite. Finally, carbonate scales are studied using the CaCO 3 sample with the XRD peaks illustrated in black and are in agreement with the published literature. , All samples were pure minerals as confirmed by the XRD results.…”
Section: Resultssupporting
confidence: 91%
“…The formation of galena is often linked to the hydrothermal alteration of leadbearing minerals in the presence of sulfur-rich fluids. Additional compounds like lead carbonate and lead sulfate can also be present in galena, depending on the location of the ore mining site [1][2][3][4][5][6]. PbS, with a lead-to-sulfur ratio of 86:13 mass percent, is found in the Japanese and American galena ores [1].…”
Section: Introductionmentioning
confidence: 99%
“…Additional compounds like lead carbonate and lead sulfate can also be present in galena, depending on the location of the ore mining site [1][2][3][4][5][6]. PbS, with a lead-to-sulfur ratio of 86:13 mass percent, is found in the Japanese and American galena ores [1]. This compound is commonly used in various practical applications, including solar energy and infrared sensors, due to its low energy gap of bulk pieces (~0.4 eV), optoelectronics, semiconductors, thermoelectric materials, and biconical uses [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Galena mainly consists of lead sulfide (PbS) and other trace elements such as silver, zinc, silicon, iron, copper, and their oxides [ 1 , 2 ]. Depending on the mining site, many types of galena with different chemical composition have been reported [ 3 ], and it has been confirmed that the richest lead and sulfur galena ores were found in the USA and Japan. As long as galena mineral is the main source of lead, it will remain the main source of PbS compounds for many applications, such as thermoelectric parts, infrared detectors, solar selective surfaces, semiconductors, and solar cells [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%